Desain Dan Analisis Resonant Converter Bertenaga Akumulator 12 Volt Sebagai Rangkaian Penggerak Lampu Led Menggunakan Matlab-Simulink - Irsyad Alfahmi; Budhi Anto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
This paper describes a design and analysis of resonant converter to LED lamp driving. The converter is powered by 12 volt battery. The type of resonant converter is equipped by a Half-Bridge LLC Series Resonant Converter. The type of battery is lead acid battery which has capacity of 12 Ah and nominal voltage of 12 volts. The purpose of series resonant converter design is to generate the requirement voltage by forming of LED lights as a load with 19 volts of voltage. The circuit has been designed and modeled then simulated using MATLAB-Simulink application to view the characteristics of the converter output voltage and current. The simulations has performed a total of 11 conditions, which are covers several condition when hit the following value: 5%, 10%, 15%, 20%, 25%, 30%, 35%, 37%, 40%, 43% and 45% of duty cycle respectively. The converter operates at 50 KHz of switching frequency. The output of the converter is connected to 13,57 Ω resistor which is equal to 20 seeds of 1 watt LED. The simulation results show the expected condition of hypotesis has been achieved i.e 19 volts of voltage and a current of 1.4 A at 43% duty cycle with an efficiency of 79.39%.Kata kunci : resonant converter, lead acid battery, LED, Matlab-Simulink.